Service Quality and Students' Satisfaction in Management Programs at Public Campus in Nepal - Bishweshwor Timalsena (The Journal of Aadikavi, 2026)
This study examined management students' perceptions of service quality and its effect on student satisfaction at a public higher education institution in Nepal, namely Aadikavi Bhanubhakta Campus. It observed the influence of service quality on the overall learning experience of students, using the SERVQUAL model. The study was quantitative and causal in nature. The structured 5-point Likert scale questionnaire was administered to 230 BBA, BBS, and MBS students chosen through simple random sampling. IBM SPSS version 27 was used to perform descriptive statistics, reliability and validity tests, and correlation and regression analysis on the data. All five SERVQUAL dimensions were positively and significantly correlated with student satisfaction. Assurance (r=.943) and empathy (r =.902) showed the strongest correlations. The combined service quality explained 81% of the variance in student satisfaction (r2 = .811). Students’ perceptions of tangibility, responsiveness, and empathy were only moderate, showing clear areas for improvement. The study demonstrates the value of service quality attributes in meeting students’ expectations in a Nepalese public management college.